EFEKTIVITAS MODEL QUANTUM LEARNING DALAM MENINGKATKAN MOTIVASI SISWA KELAS X SMA PADA PELAJARAN PPKN - Wulandari Wulandari; Achmadi Achmadi; Bambang Budi Utomo (Universitas Tanjungpura, 2019)
ABSTRACT In this research suppose to know the effectiveness of quantum learning model to increase motivation student learning in X IIS class at SMA 1 Islamiyah Pontianak in PPKn subject learning. The research method is experiment method in pre eksperimental design form and the research design One Group Pretest-Posttest design. The research subject is X IIS class of SMA 1 Islamiyah Pontianak the determination process which being the research subject is considered to the lowest motivation in student learning. The collective data tools are observation, interview, questioner and documentation base on the result of the average in pretest and post test are 77,77 and 84,04 which means there are having the differences in before and after in use the quantum learning model. Base on the data analysis in using test t, the significance result (sig. 2-tailed) is 0,000. So, the hipotesist test Ho rejected and Ha accepted, because 0,000 < 0,05. It shows the use of quantum learning is effective in learning process in PPKn subject at X IIS class of SMA 1 Islamiyah Pontianak. The effect size in students motivation learning is 0,53 in medium class category. It shows the use of quantum learning model is effective in learning process.Keywords: Effectiveness, Quantum Learning Model, Motivation in Learning, PPKn subject.